2018
DOI: 10.1021/acs.joc.7b02570
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolo[2,3-d:5,4-d′]bisthiazoles: Alternate Synthetic Routes and a Comparative Study to Analogous Fused-Ring Bithiophenes

Abstract: New synthetic methods have been developed for the preparation of 4-alkyl- and 4-aryl-pyrrolo[2,3-d:5,4-d']bisthiazole (PBTz) building blocks from 2,4-thiazolidinedione. The resulting PBTz products have been fully characterized via structural, electronic, and optical methods, thus allowing full comparison to the previously reported dithieno[3,2-b:2',3'-d]pyrrole (DTP) analogues. Such comparisons then allow a detailed discussion of the relative electronic effects of the various methods utilized to tune the prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…66 in electron transport materials as part of co-polymers or centered between two NDIs. [72][73][74][75] Compared to DTPs such as 51 (Figure 7), the nitrogen bridge in 105 decreases the LUMO levels significantly (-0.8 eV) and shifts the absorption slightly to the red. 86 The addition of electron withdrawing cyano substituents in the bridge of 120 and the installation of peripheral sulfur redox switches provides access to sulfoxides 121 and sulfones 122.…”
Section: Core Substitutionmentioning
confidence: 98%
See 1 more Smart Citation
“…66 in electron transport materials as part of co-polymers or centered between two NDIs. [72][73][74][75] Compared to DTPs such as 51 (Figure 7), the nitrogen bridge in 105 decreases the LUMO levels significantly (-0.8 eV) and shifts the absorption slightly to the red. 86 The addition of electron withdrawing cyano substituents in the bridge of 120 and the installation of peripheral sulfur redox switches provides access to sulfoxides 121 and sulfones 122.…”
Section: Core Substitutionmentioning
confidence: 98%
“…This study covers also the selenium homologue 104 for the same purpose . Pyrrolo­[2,3- d :5,4- d ′]­bisthiazoles 105 have been explored quite extensively for use in electron transport materials as part of copolymers or centered between two NDIs. Compared to DTPs such as 51 (Figure ), the nitrogen bridge in 105 decreases the LUMO levels significantly (−0.8 eV) and shifts the absorption slightly to the red.…”
Section: Structural Spacementioning
confidence: 99%
“…This analysis is consistent with recently published results. 27 Analysis of the crystal packing in 5 reveals the existence of two short intermolecular contacts, N(1)⋯S(2) (3.109(5) Å) and N(3)⋯S(2) (3.083(5) Å), which link molecules into layers parallel to the ab plane ( Fig. 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…11,17−19 In addition, our research group and others have reported the effects of introducing a nitrogen atom to bridge the thiazole units to afford the fused building block pyrrole [2,3-d:5,4-d′]bisthiazole (PBTz) (Figure 1). 20−23 We note here our gratitude to Rasmussen et al 23 for highlighting that our earlier publications had used the incorrect IUPAC name. The bridged architecture has significant effects on the electronic and structural properties of the polymer main chain.…”
Section: ■ Introductionmentioning
confidence: 99%
“…34 The detailed synthesis of 4,4′-dibromo-2,2′bis(triisopropylsilyl)-5,5′-bithiazole (3) is reported in our previously published work. 16,20,23 The new comonomers 8 and 9 were synthesized in three steps from monomer 3. Stille coupling of 3 with precursors 1 and 2 in toluene at 170 °C afforded compounds 4 and 5 in moderate yields (35−36%).…”
Section: ■ Introductionmentioning
confidence: 99%